The relative importance of rainfall, temperature and yield data for a regional scale crop model - Watson, J.; Challinor, Andrew J. (Elsevier, 2013)
When projecting future crop production, the skill of regional scale (>100 km resolution) crop models is limited by the spatial and temporal accuracy of the calibration and weather data used. The skill of climate models in reproducing surface properties such as mean temperature and rainfall patterns is of critical importance for the simulation of crop yield. However, the impact of input data errors on the skill of regional scale crop models has not been systematically quantified. We evaluate the impact of specific data error scenarios on the skill of regional scale hindcasts of groundnut yield in the Gujarat region of India, using observed input data with the GLAM crop model. Two methods were employed to introduce error into rainfall, temperature and crop yield inputs at seasonal and climatological timescales: (1) random temporal resequencing, and (2) biasing values.